If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 5) = 3(2 + 2x) Reorder the terms: 4(5 + x) = 3(2 + 2x) (5 * 4 + x * 4) = 3(2 + 2x) (20 + 4x) = 3(2 + 2x) 20 + 4x = (2 * 3 + 2x * 3) 20 + 4x = (6 + 6x) Solving 20 + 4x = 6 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 20 + 4x + -6x = 6 + 6x + -6x Combine like terms: 4x + -6x = -2x 20 + -2x = 6 + 6x + -6x Combine like terms: 6x + -6x = 0 20 + -2x = 6 + 0 20 + -2x = 6 Add '-20' to each side of the equation. 20 + -20 + -2x = 6 + -20 Combine like terms: 20 + -20 = 0 0 + -2x = 6 + -20 -2x = 6 + -20 Combine like terms: 6 + -20 = -14 -2x = -14 Divide each side by '-2'. x = 7 Simplifying x = 7
| 55/n=62-7 | | 2(x-3)+3x=91.50 | | 25/x=4/9 | | 6+k=9 | | 13y+x+7y= | | 5a+a+2a+9-6a+33= | | 2x^2+4x=400 | | x/-4=-90 | | 9p-6p=-8+11 | | A+30=2A+30 | | x^3+25x+144=0 | | b/5=30 | | 2/5w=8 | | 4+x/7=10 | | -(3y+3)-(-2y-5)=-4 | | x+-4=-90 | | 3y^2+16y=-5 | | 245=-y+183 | | -9[-2]+4f=7f-3 | | 112=120-4x | | 92/4 | | tanx*sinx+sinx=0 | | 9+(-11)=4x-3x+5 | | 5n^2-17=58 | | 13y-18=(-5)y+36 | | .75x+2-6=.5x-12 | | 3x^2-18=-18 | | 133/7 | | 2=182-x | | 6u-9u=6[-2]+u | | x*7=-350 | | 2+10x=x-7[-8] |